Acute pancreatitis and pancreatic pseudocyst: case report - Kury, Laís Albernaz (2022)
Pancreatic pseudocysts are complications secondary to acute pancreatitis and are characterized as cystic lesions where there is an accumulation of pancreatic secretion limited by fibrous tissue. They usually regress spontaneously, however, symptomatic fluid collections are submitted to endoscopic or surgical drainage. In the present report, the patient, who had a previous history of acute pancreatitis, after clinical worsening, underwent a cholangioresonance that showed a voluminous liquid collection located in the topography of the pancreas, with dimensions 16.91 x 16.87 x 11.26 cm, compatible with pancreatic pseudocyst.